Towards Hydrogen Evolution Initiated by LED Light: 2‐(1H‐1, 2, 3‐Triazol‐4‐yl)pyridine‐Containing Polymers as Photocatalyst. Issue 7 (6th February 2015) - Happ, Bobby; Kübel, Joachim; Pfeffer, Michael G.; Winter, Andreas; Hager, Martin D.; Dietzek, Benjamin; Rau, Sven; Schubert, Ulrich S.; Schubert, S.; Manners, I.; Newkome, G. R.; Schubert, U. S.
<x xml:space="preserve">Abstract</x> Two‐ and three‐component polymethacrylates, featuring a 2‐(1‐substituted‐1H‐1, 2, 3‐triazol‐4‐yl)pyridine‐based metal complex as photosensitizer, a viologen‐type electron mediator, and a triethylene glycol methyl ether as solubilizing part are synthesized by statistical reversible addition–fragmentation chain transfer (RAFT) radical polymerization allowing the construction of well‐defined copolymers. Thereby, heteroleptic ruthenium(II) and iridium(III) complexes serve as charged photosensitizers. In hydrogen evolution experiments, as proof‐of‐concept, triethylamine is utilized as a sacrificial donor and colloidal platinum as hydrogen evolving catalyst. The macromolecules bearing heteroleptic iridium(III) complexes of the general formula [Ir(ppy)2(trzpy)]PF6 (ppy: 2‐phenylpyridine; trzpy: 2‐(1‐substituted‐1H‐1, 2, 3‐triazol‐4‐yl)pyridine) and [Ir(btac)2(trzpy)]PF6 (btac: 3‐(2‐benzothiazolyl)‐7‐(diethylamino)coumarin) are photocatalytically active producing molecular hydrogen in water upon illumination at 470 nm. By changing the cyclometalating ligand from ppy to btac, the photocatalytic performance of the copolymer as reflected in the turnover number increases by two orders of magnitude. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>